Studi Analisis Pengembangan Bahan Ajar PAI di SMKN 1 Pamekasan (dalam Tinjauan Regulasi, Psikologi, dan TIK) - Miftahul Jannah (IQRO: Journal of Islamic Education, 2024)
The development of PAI teaching materials needs to consider various aspects, starting from psychological aspects (cognitive and mental abilities) to technological aspects. To analyze this, this research uses a descriptive-analytic approach, collecting data through interviews, observation and documentation methods. The research location is at SMKN 1 Pamekasan.  The results of the research show that: 1) in the student handbook entitled it was found that PAI material is generally in accordance with the regulations of Minister of Education and Culture No. 60 of 2014, but some of it is not appropriate, there is even material that does not refer to Permendikbud regulations. 2) there is some material whose explanation is inadequate and does not suit the psychological level of students, such as in the discussion of Al-Quran Principles in Establishing Laws. 3) the development of materials and application of ICT-based PAI learning is sufficient, although there are several technical obstacles.